Energy Dynamics of Rice Production in Eastern India as Influenced by Resource Conserving Establishment Methods and Weed Management - Acharya, Shivasankar; Jena, S. N.; Paikaray, R. K.; Rath, B. S.; Garnayak, L. M.; Dwibedi, S. K.; Mohapatra, B. K. (International Journal of Bio-resource and Stress Management, 2022)
The field experiment was conducted during the wet seasons of 2020 and 2021, at the Agronomy Research Farm of Odisha University of Agriculture and Technology, Bhubaneswar, Odisha, India to assess the input energy requirements and output energy production of establishment methods and weed management in rice. The treatments included three establishment methods viz., Dry-direct seeded rice (Dry-DSR), Wet-DSR and puddled transplanted rice (PTR) in main plot and six weed management treatments viz., hand weeding, oxadiargyl @ 90 g ha-1 as pre-emergence (PE) followed by (fb.) penoxsulam+cyhalofop @ 135 g ha-1 as post-emergence (PoE), oxadiargyl @ 90 g ha-1 (PE) fb. triafamone+ethoxysulfuron @ 60 g ha-1 (PoE), oxadiargyl @ 90 g ha-1 (PE) fb. bispyribac sodium @ 25 g ha-1+fenoxaprop @ 56 g ha-1 (PoE), brown manuring (DSR) / green manuring (PTR) fb. 2,4-D at 25 DAS/T and unweeded control in subplot. Dry-DSR utilised 3.2% less input energy than Wet-DSR. PTR recorded highest energy use efficiency (11.88), energy efficiency ratio (5.78), energy productivity (0.393 kg MJ-1) and energy profitability (10.88), followed by Dry-DSR and Wet-DSR. The highest specific energy (4.59 MJ kg-1) was estimated in Dry-DSR, differing significantly with other establishment techniques. Among weed management options, the highest energy use efficiency (11.89) and energy profitability (10.89) was recorded with application of oxadiargyl (PE) fb. penoxsulam+cyhalofop (PoE), being at par with hand weeding, oxadiargyl (PE) fb. bispyribac sodium+fenoxaprop (PoE). Oxadiargyl fb. penoxsulam+cyhalofop under Dry-DSR was highly economic energy efficient, but at par with oxadiargyl fb. bispyribac+fenoxaprop under the same establishment technique.